The Global Economic crisis & organisation change: case studies in the UAE - Al Hashemi, Khalid (2009)
A gain wave of corporate restructuring has rolled through the global corporate landscape ever since the 1980’s, & to date there are still no signs of it lowing down. Much of the restructuring took place under the banner of increasing corporate financial performance, but a significant byproduct of the deep-rooted organisational change it involves is additional strain on the organisation’s relationship with employees, communities, taxpayers, governments & stakeholders (Heugens, P., Schenk, H. 2004). This research is a part of the requirements of the Master of Science in Project Management program within the British university in Dubai. The research is introducing the current problem of the economy downturn due to the global financial crises happening all over the world. It is also focusing on the effect of this global crisis in the U.A.E. The literature review of the research is designed so it reflects for the reader some aspects of the international economy. It shows some history then it talks about the era of crisis & how the U.A.E. market is getting affected. Furthermore, the research shifts gradually into highlighting the affect of the economy downturn in the four major companies in the U.A.E. who are specialised in the real estate business. Sequentially to give an example for the reader on the importance of the organisational structure, a full organisational structure system of Dubai Properties Group will be presented to show the evolution of this structure firstly in accordance with the business needs to expand & secondly due to the economy downturn within the market. This shows the importance of the knowledge which has to be used to manoeuvre the restructuring of the organisation in accordance with the surrounding environment. In addition to the previous, the research presents for the reader the different types of environmental factors & their affect on the organisational structure. All of these elements should tie together in order to assure the existence of the company as a main target & then the expansion of the operation which means an increase in the profit. The out come of the research will show the different reactions of the different organisations towards the economy downturn. It will also discuss some measures to overcome the crisis & have the organisational structure of the company stabilized & functional.